Relationship of Hypothyroidism with Chronic Tension-Type Headache (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Chronic tension-type headache is not uncommon complaints among patients.Objective: This study was undertaken to assess the frequency of subclinical and over hypothyroidism in patients with chronic tension-type headache.Methodology: This study was conducted in Dhaka Medical College, Dhaka, Bangladesh. The study subjects consisted of patients presented with primary headache disorders. Thyroid function test were performed among all patients. The patients were compared with the value of thyroid hormone.Result: Among the patients 21.0% had chronic sub-type of TTH. Out of 42 chronic tension-type headache patients 12 had subclinical and another 12 had overt hypothyroidism. Statistically significant difference was seen among different sub-types of headache in relation to thyroid status.Conclusion: Hypothyroidism is found to be a co morbidity or precipitating factors to be development of chronic type of tension-type headache.Journal of National Institute of Neurosciences Bangladesh, January 2022; 8(1):38-41